Penerapan Teknik Relaksasi Genggam Jari Terhadap Penurunan Skala Nyeri Pasien Post Op Sectio Caesarea di RSIA Sitti Khadijah Kota Gorontalo - Harismayanti Harismayanti; Junita Djojohikrat; Jumriaty Thalib (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Bacground Sectio caesarea is a procedure that involves cutting the uterine and abdominal walls to deliver a fetus. This study aims to determine the application of hand-held relaxation techniques to reducing the pain scale of post-section caesarea patients at RSIA Sitti Khadijah Aisyiyah, Gorontalo City. Method : The method used is descriptive analytic with a case study approach on 4 Post sectio caesarea patients with pain at RSIA Sitti Khadijah Aisyiyah Gorontalo City which includes nursing assessment, nursing diagnosis, nursing intervention, nursing implementation and nursing evaluation. The process of applying this finger-held relaxation technique is carried out for 1 day. Measurement of the pain scale was carried out before and after the hand-held relaxation technique was carried out and using a Numeric Rating Scale (NRS) pain scale measuring instrument. Result : So the results obtained before and after the relaxation technique was carried out, the pain intensity decreased. This case study shows that after finger grip relaxation was performed in patients I, II, III, and IV who experienced postoperative sectio caesarea pain, the result was a change in the pain scale from a moderate pain scale to a mild pain scale. Conslusion : There is a significant effect of the application of finger grip relaxation techniques in post op section caesarean patients for changes in pain levels.